2020
DOI: 10.3390/s20216070
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Utility Poles in Aerial Orthoimages Using ATSS Deep Learning Method

Abstract: Mapping utility poles using side-view images acquired with car-mounted cameras is a time-consuming task, mainly in larger areas due to the need for street-by-street surveying. Aerial images cover larger areas and can be feasible alternatives although the detection and mapping of the utility poles in urban environments using top-view images is challenging. Thus, we propose the use of Adaptive Training Sample Selection (ATSS) for detecting utility poles in urban areas since it is a novel method and has not yet i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…To summarize, our results indicate that VFNET provided the highest F1-Score, followed by RetinaNet, SABL, Faster R-CNN, and ATSS. Previous studies in remote sensing [49,50] showed that ATSS provided more accurate results for pole and apple detection; however, for active fire detection, ATSS provided less accurate results due to a small rate of True Positives, indicating the inability of the trained model (considering the same number of training epochs of the remaining algorithms) to identify active fire regions.…”
Section: Qualitative Analysis and Discussionmentioning
confidence: 95%
“…To summarize, our results indicate that VFNET provided the highest F1-Score, followed by RetinaNet, SABL, Faster R-CNN, and ATSS. Previous studies in remote sensing [49,50] showed that ATSS provided more accurate results for pole and apple detection; however, for active fire detection, ATSS provided less accurate results due to a small rate of True Positives, indicating the inability of the trained model (considering the same number of training epochs of the remaining algorithms) to identify active fire regions.…”
Section: Qualitative Analysis and Discussionmentioning
confidence: 95%
“…Concerning electric poles in particular, a lot of attention has gone into ways of mapping them periodically, including manned [1] and unmanned [2] aerial flights, and remote sensing pipelines [3] (we refer to [2] for a more in-depth overview). Concerning deep learning instead, deep neural networks have been used to predict possible failures [19], identifying specific poles from images [20], or finding vegetation or icing on the poles [2]. State-of-the-art methods are generally framed as an object detection problem, where the task is to find the proper bounding box surrounding a pole from an aerial image [20].…”
Section: Related Workmentioning
confidence: 99%
“…Concerning deep learning instead, deep neural networks have been used to predict possible failures [19], identifying specific poles from images [20], or finding vegetation or icing on the poles [2]. State-of-the-art methods are generally framed as an object detection problem, where the task is to find the proper bounding box surrounding a pole from an aerial image [20]. In this article, we consider an intermediate problem, where we assume that poles have been successfully identified in multiple photos (taken from successive aerial routes, see Section III), but we need to reidentify the same pole from different images to plan potential maintenance activities.…”
Section: Related Workmentioning
confidence: 99%
“…The algorithm down samples the point cloud according to voxel size, filters the downsampled point cloud to remove data points corresponding to ground reflections, divides the point cloud into a plurality of clusters that are parallel to the vehicle’s direction of movement, projects the plurality of clusters to a plane that is parallel to the sides of the vehicle to generate an image, detects a pole‐shaped object in the image and tracks the pole‐shaped object by deep sorting across multiple frames of the plurality of frames (Chen et al, 2020). Clustering point clouds in complex city scenes with attached walls is usually time‐consuming and very challenging (Gomes et al, 2020).…”
Section: Research Reviewmentioning
confidence: 99%